Radioactive Merano SPA Treatment for Allergic Rhinitis Therapy. (8th September 2016) - Passali, Desiderio; Gabelli, Giacomo; Passali, Giulio Cesare; Magnato, Roberto; Platzgummer, Stefan; Salerni, Lorenzo; Lo Cunsolo, Salvatore; Joos, Alexandra; Bellussi, Luisa Maria
Abstract : Allergic rhinitis is a common nasal disorder with a high impact on quality of life, high social costs in therapies, and a natural development towards asthma. Pharmacological therapy is based on several genres of medications, of which intranasal corticosteroids are currently the most widespread. Thermal water treatment has traditionally been used as adjunctive treatment for chronic rhinitis and sinusitis. The present study was carried out to assess the clinical efficacy of nasal inhalation of radioactive oligomineral water vapours from the Merano hot spring and to compare it with the clinical efficacy of mometasone furoate nasal spray. A comparative prospective study was performed in 90 allergic patients treated at Merano hot springs: a group of 54 subjects treated with radioactive thermal oligomineral water and a control group of 36 subjects treated with mometasone nasal spray. Patients of both groups were assessed before and after treatment by Sino-Nasal Outcome Test questionnaire, active anterior rhinomanometry with flow and resistance monitoring, measurement of mucociliary transport time, and cytological examination of nasal brushing/scraping. The study showed that inhalation treatment with radioactive hydrofluoric thermal water for two weeks produces an objective clinical and cytological improvement in allergic patients, similar to that obtained with mometasone furoate nasal spray.